Identification method of railway public interest transportation based on National Economic Benefits. Issue 4 (3rd July 2016) - Song, J. Y.; Gong, D. Q.
Abstract: Identifying railway public interest transportation correctly is not only the requirement to ensure the healthy development of railway industry, but also the requirement for government to manage the public transport activities efficiently. Firstly, based on the analysis of the deification of railway public interest and railway public interest transportation, this paper summarizes the features of railway public interest; then through the analysis on the user benefit, supplier benefit and environmental improvement benefits, the identification method of railway public interest transportation is studied based on national economic benefits method, at last, this method is validated through the Golmud-Lhasa section of Qinghai-Tibet Railway.